Structural funds and regional convergence in Italy - Silvia Loddo (European Regional Science Association (ERSA), 2010)
The lack of convergence across Italian Regions has been widely cited as an incontrovertible proof of failure of Cohesion policy. This paper aims to provide a twofold contribution to the debate on the effectiveness of these policies in Italy. Firstly, we provide an up-to-date view of convergence across Italian regions by focussing on the period covered by regional development policies carried out by EU. Poorer regions in Italy have indeed caught up with the richer regions over the period 1994-2004 and much of this convergence process has occurred towards region-specific steady states. Secondly, we consider Structural Funds as a conditioning variable in the convergence equation by using recently available data on expenditure implemented during the Second and the Third Planning Period. Our panel estimates point to a positive and significant impact of the Structural Funds on regional convergence in Italy over the period 1994-2004. When the Structural Funds are considered individually we find that the expenditure allocated by ERDF has medium term positive and significant returns while support to agriculture has short-term positive effects on growth which wane quickly. Finally, our results cast some doubt both on the (i) distributive efficiency of resources allocated by ESF and (ii) on the effectiveness of the intervention policies in support to education, Human capital and employment.
Keywords: 330